Analysis of Hajj and Umrah Services at PT. Menara Babussalam Citra Mandiri Palu - Hasnawati Hasnawati; Rajindra Rajindra; Sirajudin Sirajudin (Universitas Muhammadiyah Palu, 2021)
The aims of this study are: (1) To find out and analyze the Hajj and Umrah services at PT. Menara Babussalam Citra Mandiri Palu, and (2) To find out and analyze the factors that support and hinder Hajj and Umrah services at PT. The Babussalam Citra Mandiri Tower in Palu. This type of research is descriptive qualitative using in-depth interviews with research informants, namely directors, managers, and employees of the HRD PT. Menara Babussalam Citra Mandiri Palu as well as several prospective hajj and umrah pilgrims according to research needs and considered to know well information about hajj and umrah services at PT. The Babussalam Citra Mandiri Tower in Palu. The results showed that: Hajj and Umrah services at PT. The Babussalam Citra Mandiri Tower in Palu is quite good, where employees serve prospective pilgrims professionally both when in the homeland and after in the holy land and can cooperate with parties who support the departure of Hajj and Umrah such as administrative services, accommodation, transportation, health, and consumption. Supporting and inhibiting factors of PT. The Babussalam Citra Mandiri Tower in Palu as well as the implementation of the Hajj and Umrah pilgrimages are barometers for achieving a goal that has been previously set by the management. Factors that support services to pilgrims are the facilities provided to pilgrims such as the types of four and five-star hotels, planes that do not transit, the presence of doctors who accompany pilgrims to provide medicines. While the inhibiting factors are complaints from pilgrims regarding the food menu provided by the hotel and sometimes flight delays due to unfavorable weather for flying.